In situ observation of circadian rhythm of polyps’ opening and closing of the coral Dendrophyllia ramea (Linnaeus, 1758) - SALVATI, EVA; PROVENZANI, CLAUDIO; D'AMBROSI, ANDREA; FINOIA, MARIA GRAZIA; ROMANO, ELENA; Canese, Simonepietro (Mediterranean Marine Science, 2023)
A widespread population of the coral Dendrophyllia ramea has been revealed southeast of Syracuse (East Sicily, Italy) at around 75 m depth. Dendrophyllia ramea is an arborescent scleractinian coral, classified as “Vulnerable” in the Mediterranean IUCN Red List and listed in Annex B of the Barcelona Convention. It is considered rare because it is seldom recorded on the Mediterranean seabed. In situ observations of two selected colonies were carried out over three months using a custom-made underwater video recording system to increase knowledge about the ecology of the species, specifically its circadian rhythm. The area was also surveyed using a special navigation system integrated into a diver propulsion vehicle to map the colonies’ position and distribution. The rhythms of the opening and closing of Dendrophyllia ramea’s polyps during the day were studied and linked to environmental factors, such as temperature, water flow, and direction. The results show that Dendrophyllia ramea opens and closes its polyps according to its circadian rhythm and water flow in analogy with other anthozoans in different environments. The opening/closing frequency analysis showed that both colonies closed at least once daily with different periodicity; one colony closed on average a few hours earlier. This project gathered important information on D. ramea’s circadian rhythm, which is relevant for improving knowledge about the ecology of this species since it provides insights into its feeding behavior, reproduction seasonality, response to environmental changes, interactions with other species, and conservation needs.